Pengaruh Pemberian Serum Albumin Manusia terhadap Kadar Albumin dalam Darah pada Anjing dengan status Hipoalbuminemia - Julita Dewitri Merthayasa; Putu Devi Devi Jayanti; Soedarmanto Indarjulianto; Ryan Hadi Permana; Nadia Liswardani Destinanda; Agustina Dwi Wijayanti (Jurnal Sain Veteriner, 2019)
Albumin consists of 50% of the total plasma protein and it is very important protein in the animal's body. Hypoalbuminemia can occurs due to various conditions, such as loss of protein nephropathy, loss of enteropathic proteins, chronic and acute diarrhea or heavy bleeding as well as malnutrition and malabsorption conditions. This study aims to determine the effect of  human serum albumin  20% infusion to increase albumin blood level in hypoalbuminemia dogs. Animals used in this study were 5 dogs whose results showed the levels of albumin below normal limits or hypoalbuminemia. Dogs with hypoalbuminemia will be infused with human serum albumin (HSA) 20% through intravenous for ± 4 hours. Then, these dogs blood will be drawn days after infusion to screen for albumin levels. The results obtained in the form of examination data of albumin blood levels in the blood before and after infusion will be analyzed with paired T-test. The results showed an increase of albumin level significantly from an average of 1.98 ± 0.356 to 2.28 ± 0.257(P <0.05). This study shows the presence of human albumin serum through intravenous infusion was able to increase albumin levels in dogs with hypoalbuminemia.